The effect of low-calorie diet on cardiometabolic risk factors in normal and overweight patients with type 2 Diabetes: a randomized controlled trial - Amiri, Roksaneh; Ayremlou, Parvin; Ansari, Samaneh; Manafi, Majid (Researcher Bulletin of Medical Sciences, 2025)
Objective: Weight loss is a basic strategy for the management of Type 2 diabetes mellitus (T2DM). Some studies have suggested that calorie restriction has beneficial effects in the management of diabetes symptoms. The aim of the present research was to evaluate the effects of a low-calorie diet (LCD) on cardio-metabolic risk factors, body composition, and liver enzymes in normal and overweight patients with T2DM. Materials and Methods: 120 eligible patients (49 female and 71 male) were randomly assigned to one of the four following groups: low caloric (LCD with -500 kcal lower than need) and isocaloric (control) diets for 12 weeks for normal and overweight T2DM patients. Glycemic and lipid profiles, liver enzymes and body composition were assessed before and after the intervention. Results: 104 patients completed the study. LCD groups presented significant decrease in anthropometric measurements compared to control groups (P<0.05). Glycemic markers, triglyceride, and alkaline phosphatase (ALP) were significantly decreased only in normal-weight LCD group compared to control group. Homeostatic model of insulin resistance, LDL-C, and ALP were significantly decreased only in overweight LCD group (P<0.05). However, insulin sensitivity was significantly increased in LCD groups compared to control groups (P<0.05). Conclusion: It was found that LCD improved cardio-metabolic risk factors, liver enzymes and body composition in normal and overweight T2DM patients.